Prevention in the Prairies: Tobacco Prevention and Sodium Reduction Initiatives in Kansas - Garvey, Jacqueline (My University, 2013)
As a Governor’s Internship award winner, I had the pleasure of working as an epidemiologist intern in the chronic disease program within the Kansas Department of Health and Environment, Bureau of Health Promotion (KDHE). The Centers for Disease Control and Prevention (CDC) awards millions of dollars each year in grants to health departments across the country and KDHE was among the top recipients of grants this past year. Specifically, I was involved with two grants given to the chronic disease program to address the major issues of tobacco use and levels of sodium in diets. Tobacco is a leading cause of death and illness in this country and efforts need to be made in reducing this reality. Heart disease is the number one cause of death in the U.S. and is directly related to sodium levels. The main CDC funded project I assisted with was a chronic disease risk reduction grant regarding tobacco prevention and cessation among all age groups across the state. This project was a statewide initiative allowing each county or group of counties to propose their own programs to reduce tobacco use. It was composed of three stages: planning, capacity building, and sustainability and maintenance. For each stage, grantees proposed programs within their own communities to prevent and reduce tobacco use. The second CDC funded project I assisted with was an observational study of sodium intake in Shawnee County, Kansas. This project produced baseline data of sodium consumption patterns in the county. The study was composed of a telephone questionnaire, a 24-hour dietary recall, and ending with educating the participants of sodium amounts. As an epidemiologist intern, I evaluated data, compiled research information, and interacted with counties regarding initiatives. Both projects allowed me to use, in a state government setting, the skills and techniques I have learned in the MPH program. These public health issues are impacting the health of Kansans, and state and local health departments are utilizing these programs to increase public awareness and decrease illness.
Keywords: Tobacco Prevention; Public Health; Sodium Reduction; Public Health (0573)